2006
DOI: 10.5713/ajas.2006.500
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Vitamin E Supplementation on Serum 慣-Tocopherol and Immune Status of Crossbred Calves

Abstract: An experiment was conducted with twenty crossbred male calves (7-15 days old) divided into 4 different experimental groups on the basis of body weights to study the effect of vitamin E supplementation on the serum α-tocopherol concentration and immune response of the calves. All the calves were fed on milk and calf starter up to 13 weeks and afterwards, they were fed on concentrate mixture and oat hay up to 32 weeks of age. In addition, the calves in groups I, II, III and IV were supplemented with 0, 125, 250 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Non-signifi cant variation in the activities of SGOT and SGPT were similar to earlier fi ndings of Samanta and Dass (2007) and Mudgal et al (2008), who did not fi nd any effect of supplemental vitamin E and Se on the activity of these enzymes in crossbred and buffalo calves, respectively. Contrary to present fi ndings, Kursa and Kroupova (1976) reported signifi cantly higher activity of SGOT and SGPT in serum of calves given extra vitamin E (15-30 mg/kg) in milk replacer.…”
Section: Discussionsupporting
confidence: 65%
“…Non-signifi cant variation in the activities of SGOT and SGPT were similar to earlier fi ndings of Samanta and Dass (2007) and Mudgal et al (2008), who did not fi nd any effect of supplemental vitamin E and Se on the activity of these enzymes in crossbred and buffalo calves, respectively. Contrary to present fi ndings, Kursa and Kroupova (1976) reported signifi cantly higher activity of SGOT and SGPT in serum of calves given extra vitamin E (15-30 mg/kg) in milk replacer.…”
Section: Discussionsupporting
confidence: 65%
“…Rise in mean ELISA antibody titer was observed from 7 DPV in all the groups which peaked on 14 days post inoculation. Contrary to this Pati (1994), Mondal (1996) and Samanta et al (2006) found the maximum ELISA titters of OAV vaccinated calves between 21 and 35 DPV, the difference may be due to species. In the present study, buffalo calves in groups II and III, which received 300 and 600 IU of DL α-tocopheryl acetate/d showed signifi cantly (P<0.001) higher antibody titer than the control group, given no supplemental vitamin E, indicating that dietary supplementation of vitamin E had humoral immune enhancing effect against killed bacterial antigen.…”
Section: Resultsmentioning
confidence: 82%
“…The cumulative group mean α-tocopherol concentration was 110.7, 206.6 and 215.8 in group I, II and III, respectively, indicating signifi cant (P<0.001) higher values in calves of group II and III as compared to control. Rapid increase in plasma α-tocopherol level in cattle calves has been reported earlier after vitamin E supplementation (Hill et al, 1993;Chatterjee et al, 2003;Samanta et al, 2006). Njeru et al (1995) reported a linear increase in serum α-tocopherol on day 3 and 14, when vitamin E was supplemented at 500, 1500 or 3000 IU/animal /day for 28 days.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations